Determinação do limiar anaeróbio por meio de biomarcadores salivares: cromogranina A como novo marcador de intensidade em natação - Jaramillo, Olga Lucia Bocanegra (2011)
CHAPTER 2: This study examined intra-individual variations in salivary lactate (sLac), alpha-amylase (sAA) and chromogranin A (sCgA) with reference to the accumulation of blood lactate (bLac) during progressive maximal exercise in swimmers. Samples of blood and saliva were collected simultaneously from 12 professional athletes during an incremental test that consisted of eight series of 100 m in front crawl with increasing velocity (0.03 m x s-1 each) and 70-sec intervals. The concentration of blood and salivary lactate was determined by an electro-enzymatic assay whereas sAA and CgA were analyzed by western blotting. Inflection point in the concentration of bLAc, sLac, sAA and CgA were found in all subjects. The accumulation of lactate in saliva followed the same pattern observed in blood with a high correlation between the two (r = 0.92). Similar results were observed between the dynamics of sAA (r = 0.81) and sCgA (r = 0.82) when compared to bLac. These findings support the usefulness of saliva for the determination of the anaerobic threshold and provide the first demonstration of sCgA as a novel marker of exercise intensity in well-trained men.